The Impact of Quantum Learning Model Type TANDUR Assisted by Quizziz Media on English Vocabulary Mastery Ability - Lesmana, Anggi Rahma Dewi; Neneng Sri Wulan, Nadia Tiara Antik Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine (1) the comparison of the improvement of English vocabulary mastery between fifth-grade students taught using the Quantum Learning Model of the TANDUR type assisted by Quizizz and those taught using the cooperative learning model Think-Pair-Share (TPS) assisted by Flash Cards and (2) the significant effect of the TANDUR model assisted by Quizizz on English vocabulary mastery. The background of this research is based on the low vocabulary mastery of elementary school students. The research employed a quasi-Experiment design with a nonequivalent control group model. The subjects consisted of 70 fifth-grade students at UPTD SDN Purwamekar. Data analysis included descriptive statistics, paired sample t-tests, N-Gain analysis, and simple linear regression. The results showed that the Experiment group's average score increased from 36 to 89, with an N-Gain of 0.817 In contrast, the control group improved from 41 to 79 with an N-Gain of 0.632. The paired t-test significance value was 0.000 (p < 0.05), and the coefficient of determination (R²) was 0.886, indicating that 88.6% of the improvement was attributed to the learning treatment. The results demonstrate that the TANDUR model, assisted by Quizizz, is effective in enhancing vocabulary mastery and is a relevant approach to be applied as an innovative, technology-based learning strategy at the elementary school level. Keywords: TANDUR Quantum type, Quizziz media, vocabulary mastery, English lesson.